IMPROVING STUDENTSâ READING COMPREHENSION OF THE TENTH GRADE CLASS AKUNTANSI 3 OF SMK MUHAMMADIYAH 2 PEKANBARU THROUGH READING ALOUD - Fitriani, Weni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This classroom action research was aimed to know whether reading aloud strategy can improve studentsâ reading comprehension of the tenth grade class Akuntansi 3 of SMK Muhammadiyah 2 Pekanbaru. This research consisted of one cycle. Thirty six students participated in this study. The data were collected from several sources; reading comprehension tests, observation sheets, and field notes. The result showed that the mean score of post test (80) was higher than mean score of pre-test (73). The observation result also showed that the there was an increase number of studentsâ participation in every single activity. We can saw that there was the increasing average number become 94.44%. It means that more than 80% of students were active in teaching and learning process. It can be conclude that reading aloud strategy can improve studentsâ reading comprehension of the tenth grade class Akuntansi 3 of SMK Muhammadiyah 2 Pekanbaru.Keywords: Reading comprehension, Reading aloud